2021
DOI: 10.5194/bg-18-2003-2021
|View full text |Cite
|
Sign up to set email alerts
|

Topography-based statistical modelling reveals high spatial variability and seasonal emission patches in forest floor methane flux

Abstract: Abstract. Boreal forest soils are globally an important sink for methane (CH4), while these soils are also capable of emitting CH4 under favourable conditions. Soil wetness is a well-known driver of CH4 flux, and the wetness can be estimated with several terrain indices developed for the purpose. The aim of this study was to quantify the spatial variability of the forest floor CH4 flux with a topography-based upscaling method connecting the flux with its driving factors. We conducted spatially extensive forest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Our study creates new understanding about high-resolution upscaling of GHG fluxes by incorporating more chamber measurements, predictors, models, and environmental gradients compared to earlier efforts (see e.g., Fox et al, 2008;Dinsmore et al, 2017;Räsänen et al, 2021;Juutinen et al, 2022;Vainio et al, 2021). For example, we included chamber measurements from 101 plots whereas earlier local-scale upscaling studies have usually had circa 30 plots.…”
Section: Methodological Considerations In Ghg Flux Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study creates new understanding about high-resolution upscaling of GHG fluxes by incorporating more chamber measurements, predictors, models, and environmental gradients compared to earlier efforts (see e.g., Fox et al, 2008;Dinsmore et al, 2017;Räsänen et al, 2021;Juutinen et al, 2022;Vainio et al, 2021). For example, we included chamber measurements from 101 plots whereas earlier local-scale upscaling studies have usually had circa 30 plots.…”
Section: Methodological Considerations In Ghg Flux Modelingmentioning
confidence: 99%
“…However, the most important environmental variables (i.e., soil moisture, temperature, biomass) had a high predictive performance. Nevertheless, future studies could explore the performance and information derived by upscaling GHG fluxes using high-resolution satellite or drone-derived remotely sensed indices directly (Siewert and Olofsson, 2020;Vainio et al, 2021;Berner et al, 2018).…”
Section: Methodological Considerations In Ghg Flux Modelingmentioning
confidence: 99%
“…It is known that, in wet enough conditions, upland soils can act as CH 4 sources, but the interesting question is what kind of spatial and temporal variation in CH 4 exchange can be expected. Within a single catchment, there can be surfaces or patches with high CH 4 emission and those with an order of magnitude lower CH 4 sink, controlled mainly by soil moisture [33]. Hence, normal spatial averaging or Lee filtering [8] to reduce speckle is not applicable.…”
Section: Introductionmentioning
confidence: 99%
“…In upland soils, highaffinity methanotrophs can consume CH 4 at atmospheric concentrations (Knief et al, 2003;Kolb, 2009). Despite the abundance of oxygen in the boreal upland forest soil, there are some indications of smaller-scale CH 4 -producing areas, such as wet depressions (Christiansen et al, 2012;Megonigal and Guenther, 2008;Vainio et al, 2021). In addition, some studies have found that upland forest soils may become CH 4 sources of varying significance after long periods of heavy precipitation (Lohila et al, 2016;Savage and Moore, 1997).…”
Section: Introductionmentioning
confidence: 99%